The impact of basic periodontal therapy on the quality of life of elderly people - Bradić-Vasić Marija; Pejčić Ana S.; Kostić Milena M.; Obradović Radmila R. (Medicinski fakultet i Klinika za stomatologiju, Niš, 2018)
The quality of life related to oral health is an important measure of the disease and the outcome of therapeutic interventions. Periodontitis is an inflammatory disease that is associated with the general state of the patient's organism and negatively affects the quality of life. The aim of this study was to examine the effect of basic periodontal therapy on the quality of life in elderly patients with periodontitis. Materials and methods: A total of 88 patients with periodontitis were randomly assigned to the group (n=44) who underwent basic therapy, while the control group (n=44) did not receive any treatment. The protocol included filling out a questionnaire OHIP-14 prior to and one month after the treatment, clinical examination and basic periodontal therapy. Patients also filled up additional questions about the gingival health as well as the impact of periodontal disease on the quality of life. Results: Clinical periodontal parameters did not show a significant difference between the groups at the beginning of the study. Improvement of all clinical parameters showing the periodontium state and a significant difference between the investigated groups (p<0.05), as well as in the treated group before and after treatment (p<0.001) was noted at the checkup. Statistically significant changes (p<0.001) like food impaction, avoiding the intake of certain foods, bad breath, avoiding laughing, and the presence of an abscess were recorded mainly in the treated group. Gingival health was rated "bad" or "very bad" with 42.73% of respondents. The impact of periodontitis on everyday activities is expressed by a simple questionnaire. All patients who answered "often" or "always" were considered to have the most common problems associated with these activities. Conclusion: The basic periodontal therapy has significantly affected the quality of life in elderly patients with periodontitis. Significant differences between the responses before and after treatment were identified.